2014
DOI: 10.1186/1475-2875-13-82
|View full text |Cite
|
Sign up to set email alerts
|

“People will say that I am proud”: a qualitative study of barriers to bed net use away from home in four Ugandan districts

Abstract: BackgroundDespite increased access and ownership, barriers to insecticide-treated bed net (ITN) use persist. While barriers within the home have been well documented, the challenges to net use when sleeping away from home remain relatively unexplored. This study examines common situations in which people sleep away from home and the barriers to ITN use in those situations.MethodsTo explore these issues, a group of researchers conducted 28 in-depth interviews and four focus groups amongst adults from net-owning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 22 publications
10
42
0
Order By: Relevance
“…Similarly, a study in Uganda identi ed outdoor biting exposure barriers, including social, logistical and access issues. In line with this study, attendance at funeral services was a signi cant limitation to LLIN use [12].Our results con rm those of Moshi et al in 2017 who pointed out that participants were frequently bitten by mosquitoes during the evening when they were outdoors, compared to when they were indoors [13]. Most participants stay outdoors in the early evening to do housework which are not possible indoors.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, a study in Uganda identi ed outdoor biting exposure barriers, including social, logistical and access issues. In line with this study, attendance at funeral services was a signi cant limitation to LLIN use [12].Our results con rm those of Moshi et al in 2017 who pointed out that participants were frequently bitten by mosquitoes during the evening when they were outdoors, compared to when they were indoors [13]. Most participants stay outdoors in the early evening to do housework which are not possible indoors.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, most respondents reported night-time communal ceremonies/gatherings, which may take more than three days. Similar observations are increasingly documented in many other malaria endemic resource-poor settings [17,43,[44][45][46]. Cooking and communal ceremonies/gatherings have been reported among the popular activities that kept people outdoors in many endemic areas of Africa notably Kilombero Valley, southern Tanzania [17,44,47], Unguja Island, Zanzibar [46], northern…”
Section: Discussionsupporting
confidence: 60%
“…Tanzania [17,44,46] and elsewhere in Africa [43,45,48], respondents reported little or no protection at all during outdoor activities at or away from home. Purportedly, the study communities experience a high risk of malaria because the documented night-time outdoor activities take long periods which may coincide with vector's peak biting time.…”
Section: Discussionmentioning
confidence: 99%
“…This may leave no spare LLINs for visitors, or for carrying during travel. In this study, other factors that may have contributed to limited use of LLINs during travel include social barriers, such as attending a funeral or wedding where individuals are expected to stay outdoors all night, or fear of appearing rude or disrespectful during communal gatherings [22]. These factors should be considered when designing strategies to increase LLIN adherence in travellers.…”
Section: Discussionmentioning
confidence: 97%
“…Although travellers may be at increased risk of malaria due to exposure to higher malaria transmission [18,19], changes in behaviour while away from home may also contribute. Some studies have suggested that individuals who travel within malaria-endemic areas may take part in outdoor activities, go to bed late, and be less likely to use LLINs, all behaviours that increase exposure to mosquitoes and risk of malaria infection [20][21][22][23]. To further explore associations between overnight travel and behaviours that might modify the risk of malaria infection, data collected over a two-year period from a cohort of individuals living in Tororo, Uganda, were analysed.…”
Section: Introductionmentioning
confidence: 99%